The Crisis : Basic Mechanisms and Appropriate Policies - Blanchard, Olivier (Washington, D.C. : International Monetary Fund, 2009)
The purpose of this lecture is to look beyond the complex events that characterize the global financial and economic crisis, identify the basic mechanisms, and infer the policies needed to resolve the current crisis, as well as the policies needed to reduce the probability of similar events in the future.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet